The mediating effect of relational capital on alliances performance of construction companies in Indonesia - Syahchari, Dicky Hida (2017)
The main objective of this research is to study the mediating effect of relational capital on alliance performance of construction companies in Indonesia. The effect of relational capital on alliance performance has become an issue of attention to most practitioners and researchers. The alliance performance is the level to which both partner companies attain their strategic goals in an alliance. Thus, a theoretical framework was developed based on the theory of the relational exchange and the resource based view theory. After identifying the gaps of previous literature, a quantitative methodology was applied by surveying respondent from 311 construction companies in Indonesia. Primary data collected by self-administered questionnaires were found to be valid and reliable when analyzed through SPSS and smart-PLS software. Based on the PLS-SEM analysis, nine hypotheses were accepted while one was rejected. Two independent variables partner fit and interdependence have shown a significant and positive influence on alliance performance. However, conflict management has a non-significant influence on alliance performance. The study also established that relational capital mediates the relationship between partner fit, conflict management, interdependence, and alliance performance. Furthermore, the essential implication of this study to the academics, construction practitioners and government or National Construction Service Board in Indonesia is to make awareness on the relational capital as a strategic factor towards accomplishing better alliance performance. It also contributes by offering good implications for construction practitioners in Indonesia, to invest more efforts in alliance performance. Limitations of the research and recommendations are presented. Finally, future study is suggested to extend this study of geographical factor and different methodology.